Arhiviranje spletnih strani v Narodni in univerzitetni knjižnici - Kavčič-Čolić, Alenka (Knjižnica, 2011)
The National and University Library (NUK) of Slovenia has been investigating web archiving methods and techniques since 2001. Under the ne Legal Deposit Law adopted in 2006, NUK is the responsible institution for harvesting and archiving the Slovenian web. In 2008 NUK started archiving the Slovenian web by making use of the web harvesting and access tools developed by the IIPC International Internet Preservation Consortium (IIPC). The paper presents the complexity of web harvesting and gives an overview of the international practice and NUK's cooperation in the IIPC consortium. Special attention is given to the analysis of public sector web content, harvested since 2008. Main goals of future developement of the web archive are an increase of harvested Slovenian web sites, the development of a user interface for public access and development of improved methods for harvesting technically problematic content.
Keywords: spletni arhivi; spletne strani; arhiviranje; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana